PERKEMBANGAN ISLAM DI AMERIKA DAN PENGARUHNYA DALAM BIDANG POLITIK - Rizka Amelia Armin (IAIN Palopo, 2022)
This study aims to determine the basis of the development of Islam in the United States and the manifestations of the influence of Islamic development in the field of United States politics, both in domestic and foreign policy of the United States. In this study a descriptive analytic method will be used which uses data collection techniques in the form of literature review, while the type of data used is theoretical data obtained from literature in the form of books, documents, journals, and information related to the problem to be studied. The data analysis technique used in this study is a qualitative analysis technique. The results of the research show that the basis for the development of Islam in the United States and its influence in the political field is based on the political system and the basic values that apply and are adhered to by the people of the United States. Islam in the United States shows rapid development both in terms of quantity and quality. In the political field, Muslims have shown an increase in involvement in political activities, for example, an increase in the number of participation in elections and also an increase in the number of partisans who are active in political party activities and an increase in cooperation and lobbying with elites and political institutions. The highest achievement of Muslims in the political field is the election of members of the congress who are Muslims. Currently there are two members of Congress who are Muslims and several of them occupy important public positions in the political and governmental structures of the United States. Muslims are also actively fighting for civil rights including political rights through Islamic organizations formed by Muslims in the United States.